Timeliness Publikasi Laporan Keuangan, Income Smoothing dan Growth Opportunities terhadap Earnings Response Coefficient - Putri, Putu Friska Devi Lionita; Wirajaya, I Gde Ary (E-Jurnal Akuntansi, 2024)
The purpose of this study was to examine the effect of timeliness of financial report publication, income smoothing and growth opportunities on the earnings response coefficient. In addition, to test differences in the timeliness of publication of financial report, income smoothing, growth opportunities and earnings response coefficient before and during the COVID-19 pandemic. The population in this study is 768 companies listed on the Indonesia Stock Exchange in 2018-2021. This study used probability random sampling technique,  which was stratified random sampling and obtained sample data of 263 companies. The data analysis technique used is multiple linear regression and paired sample T-test. The results of data analysis show that the timeliness of financial report publication and growth opportunities have a positive effect on the earnings response coefficient. Meanwhile, income smoothing has a negative effect on the earnings response coefficient. In addition, there are differences in the timeliness of publication of financial report, income smoothing, growth opportunities and earnings response coefficient before and during the COVID-19 pandemic. Keywords: Timeliness; Income Smoothing; Growth; ERC